2018
DOI: 10.3390/cryst8110400
|View full text |Cite
|
Sign up to set email alerts
|

The Study of the Mechanism of Protein Crystallization in Space by Using Microchannel to Simulate Microgravity Environment

Abstract: Space is expected to be a convection-free, quiescent environment for the production of large-size and high-quality protein crystals. However, the mechanisms by which the diffusion environment in space improves the quality of the protein crystals are not fully understood. The interior of a microfluidic device can be used to simulate a microgravity environment to investigate the protein crystallization mechanism that occurs in space. In the present study, lysozyme crystals were grown in a prototype microchannel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 64 publications
(89 reference statements)
0
2
0
Order By: Relevance
“…Generally, microfluidic devices of 100 μm in depth can be regarded as the microgravity environment. Several research groups reported the microfluidic device for protein crystal growth in microgravity and the typical optical microscope-based crystal growth analysis. , However, the mechanism and kinetics of protein crystal growth in the microfluidic device was not elucidated in detail due to limitations in measuring the crystal growth process within the device. To overcome the problem, we demonstrated real-time spectroscopy-based measurement of the protein crystal growth in the microfluidic device.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, microfluidic devices of 100 μm in depth can be regarded as the microgravity environment. Several research groups reported the microfluidic device for protein crystal growth in microgravity and the typical optical microscope-based crystal growth analysis. , However, the mechanism and kinetics of protein crystal growth in the microfluidic device was not elucidated in detail due to limitations in measuring the crystal growth process within the device. To overcome the problem, we demonstrated real-time spectroscopy-based measurement of the protein crystal growth in the microfluidic device.…”
Section: Introductionmentioning
confidence: 99%
“…In the material processing industry, the crystal growth process is an important example that the qualities of the crystal materials are closely affected by the flow instabilities resulting from the buoyancy and thermal-solutal convections, since the oscillatory flow induces impurity striations in the crystals [3,4]. Especially, under microgravity conditions, the effect of gravity is minimized [5] and the effect of thermal-solutal capillary flow generated by surface tension gradient is highlighted [6][7][8]. Czochralski (Cz) crystal growth technology is an important method for producing crystals, where a rod-mounted seed crystal dipped into melt and carefully pulled out by controlling the thermal and concentration gradients, crystal rotation and pulling rates [9,10].…”
Section: Introductionmentioning
confidence: 99%